Concomitant Ro/SSA and La/SSB antibodies are biomarkers for the risk of venous thromboembolism and cerebral infarction in primary Sjögren's syndrome. (17th June 2019) - Mofors, J.; Holmqvist, M.; Westermark, L.; Björk, A.; Kvarnström, M.; Forsblad‐d'Elia, H.; Magnusson Bucher, S.; Eriksson, P.; Theander, E.; Mandl, T.; Wahren‐Herlenius, M.; Nordmark, G.
Abstract: Background: To assess the risk of incident cardiovascular disease in patients with primary Sjögren's syndrome, overall and stratified by Ro/SSA and La/SSB autoantibody status. Methods: A cohort of patients with primary Sjögren's syndrome in Sweden ( n = 960) and matched controls from the general population ( n = 9035) were included, and data extracted from the National Patient Register to identify events of myocardial infarction, cerebral infarction and venous thromboembolism. Hazard ratios were estimated using cox proportional hazard regressions. Results: During a median follow‐up of 9.5 years, the overall hazard ratio (HR) was 1.6 (95% CI 1.2–2.1) for myocardial infarction, 1.2 (95% CI 0.9–1.7) for cerebral infarction and 2.1 (95% CI 1.6–2.9) for venous thromboembolism. Patients positive for both Ro/SSA and La/SSB autoantibodies had a substantially higher risk of cerebral infarction (HR 1.7, 95% CI 1.0–2.9) and venous thromboembolism (HR 3.1, 95% CI 1.9–4.8) than the general population. These risks were not significantly increased in Ro/SSA‐ and La/SSB‐negative patients. Among autoantibody‐positive patients, the highest HR of cerebral infarction was seen after ≥10 years disease duration (HR 2.8, 95% CI 1.4–5.4), while the HR for venous thromboembolism was highest 0–5 years after disease diagnosis (HR 4.7, 95% CI 2.3–9.3) and remained high throughout disease duration. Conclusions: Primary Sjögren's syndrome is associated with a markedly increased risk of cardiovascular disease and the presence of Ro/SSA and La/SSB autoantibodies identify the subgroup of patients carrying the highest risk. These findings suggest that monitoring and prevention of cardiovascular disease in this patient group should be considered. Abstract :